O folhetim e o livro: travessias da ficção machadiana de Quincas Borba - Pilon, Márcia Regina Scarpa (2008)
The novel Quincas Borba, written by Machado de Assis, has two different versions published in two different distinctive holders: the newspaper, as a serial publication, and the book. Both versions carry important differences that reveal the main subject observed in the present work: the formation of the reader under educative and evolutive focus, acknowledged in a comparison between the two versions. That comparison has also revealed the process of narrative composition of Quincas Borba. The investigation puts in doubt and discusses the role of the reader in the different holders, noticing that the reading attitudes vary and structure themselves in different ways in the two versions. We intended to investigate, in the first chapter, the reading in different levels of perception, or the differences between the serial publication and the book in the act of reading; in the second chapter, we searched in the novel the model of reader roused by the narrative, as much as the differences of the narrated matter in the crossing serial publication book; finally, in the third chapter, the question of the authorship and the reading in the fictional context, comprehending that the changes made between one version and the other are, in their majority, adjustments played by the author in the search of a model-reader of his work this is a question that receives enormous attention by the contemporary critics and that finds in Machado de Assis works a productive investigation to the development of the various studies about the subject. To the effective rendering of this work, it was necessary to approach theoretical hypothesis about serial publications, being Marlyse Meyer the main reference. It was also necessary to search Umberto Eco s considerations about the model-reader, a kind of reader foreseen by the author and printed in the text writing. Other aspects of the work of Machado de Assis were observed through the reading of the vast bibliography about the writer and his production, among which we detach the studies of John Gledson, Hélio Seixas Guimarães and Alfredo Bosi